Analisis instrumen penilaian kurikulum 2013 buku guru kelas V tema 8 edisi revisi 2017 berdasarkan perspektif HOTS sebagai transfer of knowledge - Fajar Kurniawan; Retno Winarni; Anesa Surya (Universitas Sebelas Maret, 2021)
The purpose of this study is to determine the assessment instrument based on HOTS perspective (Higher Order Thinking Skills) in the thematic book of the fifth grade teacher theme 8